2016
DOI: 10.1016/j.neuroimage.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of meso-limbic reward processing by motivational tendencies in young adolescents and adults

Abstract: Adolescence is a particularly vulnerable period for the onset of substance use disorders and other psychopathology. Individual variability in motivational tendencies and temperament and significant changes in functional brain organization during adolescence are important factors to consider in the development of substance use and dependence. Recent conceptualizations suggest that sensitivity to reward is heightened in adolescence and that this motivation tendency may precipitate subsequent substance abuse. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…A direct comparison of Big Win versus Neutral and Big Loss versus Neutral anticipation contrasts revealed negligible differences between the activation in the VS and insula in the group‐level activation maps, and only a small Win‐related increase in activation in the mPFC. This similarity in activation profiles during anticipation of both positive and negative stimuli is consistent with a recent meta‐analysis demonstrating that approach and avoidance behavior have considerable overlap in activation (Oldham et al., 2018), and other studies reporting similar activation patterns in young adults (Joseph et al., 2016; Murray et al., 2020) and populations at risk to substance use (Bjork et al., 2008). The similarity in the neural activation to the anticipation of Big Win and Big Loss cues is also consistent with the hypothesis that certain regions may display roughly equivalent activation at the extreme ends of value (Bartra et al., 2013).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A direct comparison of Big Win versus Neutral and Big Loss versus Neutral anticipation contrasts revealed negligible differences between the activation in the VS and insula in the group‐level activation maps, and only a small Win‐related increase in activation in the mPFC. This similarity in activation profiles during anticipation of both positive and negative stimuli is consistent with a recent meta‐analysis demonstrating that approach and avoidance behavior have considerable overlap in activation (Oldham et al., 2018), and other studies reporting similar activation patterns in young adults (Joseph et al., 2016; Murray et al., 2020) and populations at risk to substance use (Bjork et al., 2008). The similarity in the neural activation to the anticipation of Big Win and Big Loss cues is also consistent with the hypothesis that certain regions may display roughly equivalent activation at the extreme ends of value (Bartra et al., 2013).…”
Section: Discussionsupporting
confidence: 85%
“…Although the MID task has been used extensively to study dysfunctional reward processing in populations with substance use disorders (Balodis & Potenza, 2015), it has also been incorporated into other studies of neurodevelopment and broader psychopathology. Various versions of the MID task have been used to investigate reward‐related changes as a function of age (Bjork et al., 2010; Dhingra et al., 2019; Heitzeg et al., 2014), social versus nonsocial rewards (Schwartz et al., 2019), psychosocial characteristics of impulsivity and sensation seeking (Büchel et al., 2017; Cao et al., 2019; Joseph et al., 2016), early adversity (Boecker et al., 2014; Gonzalez et al., 2016), substance use (Aloi et al., 2019; Cope et al., 2019; Heitzeg et al., 2014; Karoly et al., 2015; Nestor et al., 2019; Sauder et al., 2016; Swartz et al., 2019), depression (Chan et al., 2016; Colich et al., 2017; Landes et al., 2018; Mori et al., 2016), and other psychiatric symptoms (Bourque et al., 2017; Lancaster et al., 2016; Maresh et al., 2019; Mikita et al., 2016; Papanastasiou et al., 2018; von Rhein et al., 2015; Stevens et al., 2018; Urošević et al., 2016; Veroude et al., 2016; Xu et al., 2017). Across these studies, a wide range of brain‐behavior effects are reported.…”
Section: Introductionmentioning
confidence: 99%
“…A direct comparison of Big Win and Big Loss anticipation phases revealed negligible differences between the activation in the NAcc and insula in the group level activation maps, and only a small Win-related increase in activation in the mPFC. This similarity in activation profiles during anticipation of both positive and negative stimuli is consistent with a recent meta-analysis demonstrating that approach and avoidance behavior have considerable overlap in activation (Oldham et al, 2018), and prior studies reporting similar activation patterns in young adults (Joseph et al, 2015;Joseph et al, 2016) and substance use populations (Bjork et al, 2008). Although prior models suggested that levels of uncertainty, depending on positive or negative arousal, would elicit activation in the NAcc or insula (Knutson & Greer, 2008), these difference were not apparent during the anticipation phase.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to improving power, researchers would benefit from assessing how the MID contrast values fit in a larger nomological network of neural and behavioral constructs, beyond an abstract subtraction processes that presumes a process of motivation or consumption of reward (Poldrack & Yarkoni, 2016). One approach may be to use parametric modulators, which has been used in prior analyses, but is largely underutilized (Aloi et al, 2019;Joseph et al, 2016). In addition to improving estimates of functional parcels (Nikolaidis et al, 2020), multivariate pattern analyses may help with the reproducibility of theorized cognitive processes (Hong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation